2000
DOI: 10.1002/(sici)1097-4652(200002)182:2<256::aid-jcp15>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Functional discontinuities in prothymosin ? caused by caspase cleavage in apoptotic cells

Abstract: Our study examines the effect of apoptosis on prothymosin alpha, an abundant, nuclear protein intimately involved with proliferation of all mammalian cells. When HeLa cells were treated with actinomycin D, with etoposide, or with staurosporine following synchronization with hydroxyurea, they underwent apoptosis based on several specific criteria, including fragmentation of DNA and activation of specific caspases. Similarly treated NIH3T3 cells arrested and displayed no indicators of apoptosis. In HeLa, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 70 publications
1
12
0
8
Order By: Relevance
“…When rat ProTa was treated with active caspase-3, a 13 kDa protein band was time dependently generated in a zDEVD-fmk-reversible manner (Figure 6c). This finding is consistent with reports that human ProTa has three overlapping caspase-3 cleavage sites, 94DDED97, 95DEDD98, and 97DDVD101, 20,21 immediately upstream of the NLS moiety in its C-terminus, and that this fragment lacks an NLS moiety KKQK, which is present in rat ProTa at amino-acid positions 103-106. To identify the cleavage sites of rat ProTa by active caspase-3, we performed MALDI-TOF analysis.…”
Section: S100a13-dependent Non-vesicular Release Of Prota H Matsunagasupporting
confidence: 92%
See 1 more Smart Citation
“…When rat ProTa was treated with active caspase-3, a 13 kDa protein band was time dependently generated in a zDEVD-fmk-reversible manner (Figure 6c). This finding is consistent with reports that human ProTa has three overlapping caspase-3 cleavage sites, 94DDED97, 95DEDD98, and 97DDVD101, 20,21 immediately upstream of the NLS moiety in its C-terminus, and that this fragment lacks an NLS moiety KKQK, which is present in rat ProTa at amino-acid positions 103-106. To identify the cleavage sites of rat ProTa by active caspase-3, we performed MALDI-TOF analysis.…”
Section: S100a13-dependent Non-vesicular Release Of Prota H Matsunagasupporting
confidence: 92%
“…4 Furthermore, there is a report that ProTa is released from the nuclei when the NLS is cleaved off by caspase-3. 20,21 This study clearly showed that the C-terminal region of ProTa including NLS is cleaved in culture by the apoptosis-induced compound, and in cell-free digestion of recombinant ProTa by active caspase-3 (Figure 6d-g). As ProTa devoid of C-terminal region (a.a.98 or 99-112) is conceived to lose the activity of interaction with S100A13 (Figure 4d), it will remain in the cytosol without extracellular release.…”
Section: Discussionmentioning
confidence: 73%
“…Proteolysis of ProT␣ at the Asp 99 residue by caspase 3 has recently been reported to occur in HeLa cells in which apoptosis has been induced (35,36). This proteolysis has so far not been demonstrated to be a generalized process occurring in other cell types undergoing apoptosis and, in any case, occurs in an entirely different biological context (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In contradiction, many studies have also supported proTα's cytoplasmic localization (Sburlati, Manrow, & Berger, 1990;Tsitsiloni, Yialouris, Sekeri-Pataryas, & Haritos, 1989). In an effort to address this antiphasis, Enkemann and coworkers demonstrated that proTα is in principle detected at active transcription sites in the nucleus, while a smaller fraction remains in the cytoplasm (Enkemann, Wang, Trumbore, & Berger, 2000). It was additionally suggested that, owing to its small size and its negative charge, proTα may facilitate the movement of other positively charged molecules (eg, of histones) into and within the nucleus, particularly in highly charged environments where there is a need to overcome electrostatic interactions.…”
Section: Protα: Major Structural Characteristics and Propertiesmentioning
confidence: 99%